THE EFFECT OF SIMULATION TECHNIQUE ON STUDENTS’ SPEAKING ABILITY (A Study at The Ninth Grade of SMP Negeri 2 Angkola Selatan in 2020/2021 Academic Year) - Enon Sartika Situmeang (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract : The purpose of this research is to find: 1)the application of simulation technique. 2) the students’ speaking ability before and after using simulation technique. 3) the significant effect of simulation technique on students’ speaking ability at the IX grade of SMP Negeri 2 Angkola Selatan. Method of the research is experimental. The population of this research are all of the ninth grade students of SMP Negeri 2 Angkola Selatan. The consist 123students. Purposive sampling technique was uses to get a sample the consist 30 students. The technique for collecting data by observation sheet and giving test. The result of the application of Simulation Technique is 3.7, categorized “Very Good”.The result before using Simulation Technique 36.3, categorized “Fail”. While the students’ speaking ability after Simulation Technique is 65.1, categorized “Enough”. T-test is 12.85 and t-table is 2.04 it means that there is a significant effect of using Simulation Technique on students’ speaking ability at the ninth grade students of SMP Negeri 2 Angkola Selatan 2020/2021 Academic Year) Keyword: Simulation Technique, Technique, Speaking